Breastfeeding women's attitudes towards and acceptance and rejection of COVID-19 vaccination: Implementation research. Issue 6 (3rd February 2023) - Chawanpaiboon, Saifon; Anuwutnavin, Sanitra; Kanjanapongporn, Attapol; Pooliam, Julaporn; Titapant, Vitaya
Abstract: Objective: There are few data on lactating women's concerns about receiving COVID-19 vaccination during breastfeeding. This research investigated breastfeeding women's attitudes towards and acceptance or rejection of vaccination. Materials and methods: This prospective, descriptive, implementation study was conducted in the postpartum ward of Siriraj Hospital, Bangkok, Thailand. In Phase I, 40 breastfeeding women in the postpartum ward at Siriraj Hospital who were willing to participate in the study were interviewed. Phase II comprised questionnaire development and data validation. The combined multiple choice and scaling questionnaires designed based on the results from comprehensive interviews of phase I were used in the study. The questionnaire was administered to 400 participants in Phase III. Main outcome measures: Breastfeeding women's attitudes towards and acceptance and rejection of COVID-19 vaccination. Results: The vast majority of participants (372/400 [93.0 %]) were vaccinated predelivery. Most of the subgroup of women rejecting vaccination while breastfeeding were unsure whether too frequent vaccination would harm their unborn child (52/99 [52.5 %]; crude odds ratio [cOR], 6.50; 95 % CI, 1.47–28.68; P < 0.001). The level of immunity to the COVID-19 virus did not influence their vaccination decisions (19/99 [19.2 %]; cOR, 2.38; 95 % CI, 1.26–4.47; P < 0.001). Multivariable analysis found a significant association for women agreeing with the proposition that vaccination during pregnancy should not be performed (adjusted odds ratio [aOR], 4.83; 95 % CI, 1.41–16.57; P = 0.043). Most women who rejected vaccination knew its benefits (aOR, 31.84; 95 % CI, 7.16–141.65; P < 0.001). Conclusions: Breastfeeding women generally believed that vaccines reduce infection and disease severity. The women's COVID-19 immunity levels did not affect their acceptance or rejection of vaccination. Some mothers rejected vaccination because of concerns about possible harm to them or their newborns.